2008
DOI: 10.1136/ard.2007.079970
|View full text |Cite
|
Sign up to set email alerts
|

A modified Delphi exercise to determine the extent of consensus with OMERACT outcome domains for studies of acute and chronic gout

Abstract: Consensus is that the following domains be considered mandatory for acute gout studies: pain, joint swelling, joint tenderness, patient global, physician global, functional disability; and for chronic gout studies: serum urate, gout flares, tophus regression, health-related quality of life, functional disability, pain, patient global, physician global, work disability and joint inflammation. Several additional domains were considered discretionary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(48 citation statements)
references
References 11 publications
1
45
0
2
Order By: Relevance
“…The on November 26, 2015 -Published by www.jrheum.org Downloaded from swelling 9 . For both chronic and acute gout, the suggested variables in the OMERACT core domain set mentioned above may be evaluated by US.…”
Section: Journal Of Rheumatologymentioning
confidence: 99%
“…The on November 26, 2015 -Published by www.jrheum.org Downloaded from swelling 9 . For both chronic and acute gout, the suggested variables in the OMERACT core domain set mentioned above may be evaluated by US.…”
Section: Journal Of Rheumatologymentioning
confidence: 99%
“…Dans la goutte aiguë, il s'agit de la douleur, du gonflement et de la sensibilité articulaire à la palpation, de l'évaluation par le patient et le médecin, et de la limitation des activités. Dans la goutte dite chronique, des outils comme ceux évaluant la taille de tophus, les lésions destructrices et les échelles de handicap et de qualité de vie ont été approchés [3,13].…”
Section: Critères De Suiviunclassified
“…1 [14]. Although identified prior to the development of filter 2.0, these domains are aligned with the domain structure proposed by the OMERACT filter 2.0 [15].…”
Section: The Omeract Processmentioning
confidence: 99%
“…OMERACT has previous identified serum urate (SU) as an important outcome measure in chronic gout studies, which is understandable given that the underlying biochemical abnormality in gout is hyperuricaemia [5,14]. Despite all guidelines recommending a treat to a SU target, there is a remarkably small literature that clearly shows that changes in SU in response to treatment are associated with clinically relevant outcomes in randomised controlled trials, with only a trial of pegloticase correlating changes in SU with health-related quality of life and an observational study that showed velocity of tophus regression was associated with degree of urate lowering [1••, 25].…”
Section: Serum Uratementioning
confidence: 99%